StarDance: the evolution of exotic stars in star clusters - Pancino, Elena (Il Colle di Galileo, 2024)
StarDance is a project recently awarded a Euro 2.4 million Advanced Grant by the European Research Council. The goal of this project is to connect apparently unrelated populations of “exotic” stars which are abundant in star clusters.